Efektivitas Antibakteri Ekstrak Etanol Kulit Jeruk Manis (Citrus sinensis (L).) Terhadap Pertumbuhan Bakteri Penyebab Jerawat Staphylococcus epidermidis - Fitratul wahyuni; Dhea Frediriva Anuar; Nawwar Irfan; Efilia Meirita; Reza Laila Najmi; Najmi Hilaliyati; Izza Aulia Rizqika Nasution (LPPM, Universitas Muhammadiyah Riau, 2026)
Acne (Acne vulgaris) is a skin condition frequently caused by the bacterium Staphylococcus epidermidis. Sweet orange peel (Citrus sinensis (L.)) is an agricultural waste product with potential as a natural antibacterial agent due to its content of various secondary metabolites. This study aimed to determine the Minimum Inhibitory Concentration (MIC), Minimum Bactericidal Concentration (MBC), and antibacterial activity of the ethanolic extract of sweet orange peel against the growth of Staphylococcus epidermidis. The study employed the maceration method using 70% ethanol as the solvent. Standardization was conducted through specific and non-specific parameter tests. The MIC was determined using the broth dilution method with a UV-Vis spectrophotometer at concentrations of 6%, 7%, 8%, and 9%, while the MBC was determined using the subculture method on Nutrient Agar medium. Antibacterial activity was assessed using the disc diffusion method at concentrations of 10%, 20%, and 30%. The results showed that the crude drug material (simplicia) and the extract tested positive for alkaloids, flavonoids, saponins, tannins, and terpenoids. Values ​​for loss on drying and total ash content met quality requirements (<10%). Both MIC and MBC values ​​were observed at a concentration of 9%. The average inhibition zone diameters at concentrations of 10%, 20%, and 30% were 10.01 mm, 13.96 mm, and 18.06 mm, respectively, indicating strong inhibitory activity. It is concluded that the ethanolic extract of sweet orange peel (Citrus sinensis (L.)) possesses strong antibacterial activity against Staphylococcus epidermidis and has the potential to be developed as a natural agent for acne treatment.